Synthesis And Characterization Of Lanthanum Oxide-Polyvinyl Alcohol Phosphor Nanofibers For White Light-Emitting Diode (Wled) - Abdul Wahab, Hasmaifarahatul Hidayah (2022)
This study involves the novel application of La2O3-PVA as phosphor nanofibers for white light-emitting diode (WLED). The synthesized of La2O3-PVA phosphor nanofibers by electrospinning process were then applied as phosphor to produce white light. The chromaticity coordinates (CIE), correlated color temperature (CCT) and color rendering index (CRI) value were obtained. The potential of La2O3-PVA phosphor nanofiber was investigated by using three parameters which are different sizes of needle diameter, different thicknesses of nanofiber, and different annealing temperatures. The La2O3-PVA phosphor nanofibers were synthesized on glass substrates using electrospinning process at a distance of 17 cm from the nozzle tip, 11.7 mm diameter of the syringe, 17 kV of voltage supply with a flow rate of 0.5 ml/hour. Five different sizes of needle diameter were used to obtain the most stable and uniform nanofiber. Different thicknesses of La2O3-PVA phosphor nanofibers were prepared using 2, 4, 6, and 10 ml volume of precursor solution with thickness of 2.0, 6.0, 13.0, and 59.0 μm, respectively.